2020
DOI: 10.3390/antibiotics9060285
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Humans and Animals: Rapid Review of Psychological and Behavioral Determinants

Abstract: A rapid review of current evidence examining psychological issues regarding the use of antibiotics and antimicrobials and resistance to these in both human and animal populations was conducted. Specific areas of interest were studies examining psychological determinants of AMR and interventions which attempt to change behavior with regard to AMR in the general population; animals; and fish, in particular. Although there is some evidence of the effectiveness of behavior change in general human populations, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Therefore, greater engagement of farmers and veterinary professionals is critically important to regain confidence in the quality of local services provided and to establish a working relationship. When advice is given, there may be other anthropological, socio-cultural, economic, and environmental factors that influence farmers' behavior, as demonstrated in other studies ( 4 , 13 , 16 , 17 , 43 , 57 ). Therefore, these factors need to be taken into consideration when developing AMS programmes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, greater engagement of farmers and veterinary professionals is critically important to regain confidence in the quality of local services provided and to establish a working relationship. When advice is given, there may be other anthropological, socio-cultural, economic, and environmental factors that influence farmers' behavior, as demonstrated in other studies ( 4 , 13 , 16 , 17 , 43 , 57 ). Therefore, these factors need to be taken into consideration when developing AMS programmes.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have reported better understanding of AMU and AMR amongst farmers in developed countries compared to developing countries ( 16 , 17 ). Although some studies have suggested improving farmers knowledge through education optimizes responsible AMU, there is a mismatch between perceived knowledge and understanding, and practice ( 16 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a dearth of evidence on psychological determinants of behavior with regard to AM usage in all food animals [ 3 , 4 ]. Our recent review of determinants of AM usage in both humans and animals [ 5 ] found that awareness of AMR in farmers of both terrestrial and aquatic food animals was often poor, especially in developing countries [ 6 , 7 ]. Further, good knowledge of AMR did not necessarily translate into reduced AM usage [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of proper prescriptions, misuse of antibiotics by health professionals, low drug quality, and the inappropriate disposal of expired antibiotics add to the problem's complexity. The problem's extent seems to be aggravated because of psychological, cultural, and behavioral practices such as current lifestyles, attitudes, the misconception on the antimicrobial effects of drugs, and public's knowledge and beliefs about antibiotic resistance [34][35][36][37][38]. Once in the water, antibiotics and ARB multiply and spread their presence to other environmental compartments.…”
Section: Introductionmentioning
confidence: 99%